204k views
1 vote
Work out (8 x 10^-3) * (2 x 10^-4)
Give your answer in standard form.

2 Answers

1 vote

Answer:

(8×10^-3)( 2×10^-4)

=(8)(2)× 10^-3× 10^-4

=16× 10^-7

User Ashish Chaurasia
by
4.7k points
6 votes

The result of the expression is 0.0000016

Using the expression given :


  • (8 * 10^(-3)) * (2 * 10^(-4))


(8 * 10^(-3)) = 8 × 0.001 = 0.008


(2 * 10^(-4)) = 2 × 0.0001 = 0.0002

Multiply :

0.008 * 0.0002 = 0.0000016

Hence, the result of the expression is 0.0000016

User Cyan
by
4.6k points